2017
DOI: 10.5194/acp-2017-697
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Simulation of fine organic aerosols in the western Mediterranean area during the ChArMEx 2013 summer campaign

Abstract: especially at several hundred meters height from the surface; however over the Gulf of Genoa near the surface, the anthropogenic origin is of similar importance. A general assessment of other species was performed to evaluate the robustness of the simulations for this particular domain before evaluating OA simulation schemes. It is also shown that the Cap Corse site presents important orographic complexity which makes comparison between model simulations and observations difficult. A method was designed to est… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
5
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3
1

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 51 publications
2
5
0
Order By: Relevance
“…The model performances presented above compare well to other studies (Kim et al, 2013;Cholakian et al, 2017). In this study, for ECMWF and WRF-Lon-Lat during the summers of 2012 and 2013, RMSE ranges between 1.5 K and 3.2 K for for wind speed, and between 58…”
supporting
confidence: 86%
See 2 more Smart Citations
“…The model performances presented above compare well to other studies (Kim et al, 2013;Cholakian et al, 2017). In this study, for ECMWF and WRF-Lon-Lat during the summers of 2012 and 2013, RMSE ranges between 1.5 K and 3.2 K for for wind speed, and between 58…”
supporting
confidence: 86%
“…Over the Mediterranean region, uncertainties due to meteorology and transport may strongly impact pollutant concentrations, because the basin is influenced by pollution transported from different regions, 25 such as dust from Algeria, Tunisia and Morocco as well as both biogenic and anthropogenic species from Europe Denjean et al, 2016). Chrit et al (2017) and Cholakian et al (2017) showed that although organic aerosol concentrations at a remote marine site of the western Mediterranean are mostly of biogenic origin, they are strongly influenced by air-masses transported from the continent and by maritime shipping emissions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The central coordinates of this cell at which concentrations are computed are 42 • 52 N, 9 • 22 30 E, which is very close to the station and with a similar altitude above sea level (494 m). Cholakian et al (2017) studied the difficulty to correctly represent in a model the orography of Ersa site, which is a cape at the northern edge of Corsica. They concluded that the representativeness error is about 10 % for organic aerosols.…”
Section: Measured Datamentioning
confidence: 99%
“…Both the mechanistic and empirical approaches are scientifically valid and complementary; as shown by Kim et al (2011a), the most important aspect of an SOA model is its comprehensiveness in terms of the precursors and processes being treated (completeness of the precursor VOC list, importance of low-NO x vs. high-NO x regimes, treatment of hydrophilic properties of the surrogates) rather than its fundamental design. Cholakian et al (2017) study how the VBS approach can be used to represent the formation of SOA over the western Mediterranean and point out the importance of taking into account fragmentation and formation of nonvolatile SOA in this framework.…”
Section: Introductionmentioning
confidence: 99%